Ahmatnijar: URGENSI PEMBAHARUAN DALAM IJTIHAD FIQH: TELAAH HISTORIS DAN MODEL IJTIHAD KONTEMPORER A - Ahmat nijar (Universitas Islam Negeri Mataram, 2018)
Abstract: The Prophet Muhammad SAW has already started the ijtihadpertice which is inspiring and do the regeneration to friend of the prophet. Ijtihad as an Islamic law developmend mover machine goes with full of dynamics and always needs touch of renewal. Ijtihad fiqh renewal deals with a great struggle to rebuild arrange, recover the directions, mind set, or religious practice which involve real directing all obilities (bazl al-wus’i) to get practical syar’i through istinbath in facing contemporary dynamic challenge. This renewal must a futuristic ijtihad fiqh proces, not turn to a past process through qiraat al-mukarrah and it is expected can decorate the reportoine of old civilizations. Istinbath method which was applied was by combining nash text, sarwah fiqhiyah, , and ICT sistematically to bear an actual, futuristic, inspiring, and humanist fiqh fardli or fiqh taqdiry